P2P decision support system for cooperative electrical energy distribution network management - Vieira, Gaspar Gonçalves (2012)
Nowadays, electricity distribution companies have already performed great investments in order to identify and calculate energy losses along the distribution network. Although that big effort, the applications and approaches for clearly identifying and solving the related problems still remain too poor and inefficient. The accurate identification and the precise calculation of electricity losses enables the clear specification of the critical points and segments in the networks and, consequently, the effective prioritization of actions and interventions in order to reduce those electricity losses and problems. Although some researchers and companies have already carried out work on this issue, the existing approaches focus almost only on empirical and probabilistic data. There is still a clear gap between real information and the considered one, which tends to be poor and imprecise. Due to this reality and the lack of appropriate software applications, in this paper we propose a P2P system for the management of the whole network of electricity distribution, from medium voltage down to low voltage, including billing and other functions processing on the transformation centers, electricity losses calculation and proposals for solving actions.